2023
DOI: 10.3389/fendo.2023.1163771
|View full text |Cite
|
Sign up to set email alerts
|

Effects of distinct Polycystic Ovary Syndrome phenotypes on bone health

Abstract: Polycystic Ovary Syndrome (PCOS) is a highly prevalent and heterogenous endocrinopathy affecting 5-18% of women. Although its cardinal features include androgen excess, ovulatory dysfunction, and/or polycystic ovarian morphology, women often display related metabolic manifestations, including hyperinsulinaemia, insulin resistance, and obesity. Emerging data reveal that the hormonal alterations associated with PCOS also impact bone metabolism. However, inconsistent evidence exists as to whether PCOS is a bone-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 149 publications
0
4
0
Order By: Relevance
“…Despite the variety of criteria available, there is no agreement on the most suitable or precise criteria for diagnosing PCOS. Additionally, different criteria may lead to the identification of distinct subgroups of women with PCOS [ 7 ], complicating the use of EHRs in identifying the condition in large epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the variety of criteria available, there is no agreement on the most suitable or precise criteria for diagnosing PCOS. Additionally, different criteria may lead to the identification of distinct subgroups of women with PCOS [ 7 ], complicating the use of EHRs in identifying the condition in large epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperandrogenemia, high estrogen concentration, hyperinsulinemia, and a tendency to increase body mass index (BMI) help protect PCOS patients from osteoporosis, and the propensity to fractures decreases [5]. In previous studies, hyperandrogenemia, seen in approximately 75% of patients with PCOS, has been shown to positively affect bone by connecting to bone-related androgen receptors or indirectly by converting to estrogen through peripheral aromatization [6].…”
Section: Introductionmentioning
confidence: 99%
“…This released molecule also has a resorptionincreasing effect on osteoclasts. These hormones trigger osteoblast transformation and increase extracellular matrix production and mineralization [5]. Although these hormones positively impact bone individually, their effects on bone in the impaired hormonal and metabolic environment in PCOS are controversial.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation